Dubious victory : the reconstruction debate in Ohio - Sawrey, Robert D. (Robert Dixon) (The University Press of Kentucky, 2015)
""To the victors belong the spoils"" is a time-honored cliche. When in 1865 northern armies defeated the greatest challenge ever posed to the Union, issues of spoils and peace terms dominated public debate. But precisely what did the victorious North want from the Reconstruction process? Historians generally have shown far less interest in northern goals than in what terms southerners were willing to accept. Robert Sawrey now seeks to redress the balance by examining the post-Civil War attitudes of a representative northern state, Ohio. Sawrey's probing study explores precisely what the key iss.